Colour variation and polymorphism in the Giant orb-weaving spider Nephila vitiana (Araneae: Nephilidae) from Lombok, Indonesia - Suana, I. Wayan; Sunarpi, Haji; Sofian-Azirun, Mohd; Hashim, Rosli; Lim, Phaik Eem; Yong, Hoi Sen (Akademi Sains Malaysia & Confederation of Scientific & Technological Association in Malaysia (COSTAM), 2011)
The Giant orb-weaving spider Nephila vitiana occurred in large number in a patch of mangrove vegetation in Gili Meno, Lombok, Indonesia. Two abdominal (opisthosomal) colour morphs – yellow and greenish-yellow – were present in adult female spiders. They were equally abundant. A single female of the yellow morph was found in Sekotong on the main Lombok Island. The dorsum of the abdomen in the yellow morph was decorated with five pairs of sigillae. In the greenish morph, the dorsum was marked with five pairs of white-spotted sigillae or yellow spots. The present observation does not show unequivocally the association of colouration with habitat usage. Whether yellow colour in N. vitiana confers a selective advantage remains to be verified. The juvenile female spiders have different colour pattern from the adults.